What did Ottoman doctor Huseyin Hulki (1862-1894) speak about at the first International Dermatology Congress? - Hayirlidag, Mustafa (Galenos Publ House, 2023)
The first international congress for dermatology was held in Paris in 1889. This was the same year as the 100th anniversary of the French Revolution, which was being celebrated in Paris with the construction of the Eiffel Tower, a symbol of the country. Dermatology Congresses have been developing since the beginning and continue today. Dr. Huseyin Hulki Bey is a physician who has not only contributed to the history of world medicine, but also to the history of Turkish medicine. During his attendance at the first dermatology congress, he presented an alternative treatment for syphilis than that which was known in Ottoman medicine at the time. In this study, the speech of Turkish physician Huseyin Hulki Bey, who attended the first dermatology congress in history, is investigated.
Osmanlı hekimlerinden Hüseyin Hulki Bey (1862-1894) İlk Uluslararası Dermatoloji Kongresinde ne konuştu?
Keywords: Huseyin Hulki; dermatology; congress; Paris Medical Congress; history of medicine